Hubungan Lama Menderita Diabetes Melitus dengan Kejadian Luka Kaki Berulang di Klinik PKU Muhammadiyah Kitamura Pontianak - Kharisma, Firman; Budiharto, Ichsan; Fahdi, Faisal Kholid (Universitas Muhammadiyah Jember, 2023)
Diabetes Mellitus is a non-communicable disease that causes death. People living with DM are at risk for life-threatening complications, causing an increased need for medical care, decreased quality of life, and stress on the family. Diabetes mellitus can cause very dangerous complications for the body, namely peripheral neuropathy which can lead to the appearance of diabetic foot ulcers. Patients with diabetes who have long been diagnosed, glucose levels in the blood are no longer under control which causes atherosclerosis so that the leg muscles are disturbed. This condition is suspected of causing diabetic foot ulcers in diabetic patients. The aim of the study was to analyze the relationship between the duration of suffering from DM and the incidence of recurrent leg injuries at the Clinic PKU Muhammadiyah Kitamura Pontianak. This research method uses quantitative research with a correlational design with the quota sampling method. The population of this study were diabetic leg wound patients with a total of 86 respondents. The results of the study with a total of 71 respondents had a significant relationship between the length of time they had diabetes and the incidence of recurrent leg injuries. The conclusion of this study is that 88% of patients with long-suffering >10 years experience frequent foot wounds and have a significant relationship between the length of time they suffer from diabetes mellitus and the incidence of recurrent foot injuries at the Clinic PKU Muhammadiyah Kitamura Pontianak.